Fabrication and engineering properties studies on lightweight green concrete - Choong, Derekthy Kah Jian (2019)
High global emission of carbon dioxide (CO2) has considered as one of the significant environmental problems which caused the global warming problem and affected the ecosystem. According to the research study of Andrew (2018), it is approximately 1500 million tons CO2 emission from the cement production which is approximately 5 percent of the global CO2 emission. Next, the waste glass bottle, also known as one of the environmental problems which have occupied most space of the landfill as waste glass, is non-biodegradable material. According to the research study of Kara and Korjakins (2012), the glass has pozzolanic effect in the state of excellent powder which can help to enhance the mechanical and durability properties of the concrete as it contains a high amount of silica. Besides, titanium dioxide (TiO2) is a standard white pigment which usually used in painting, printing inks, plastic, cosmetics, food, and others. Titanium Dioxide can be applied in multiple fields due to its non-toxic, nonreactive, and glowing properties. According to Yurtoglu (2018), titanium dioxide has a pozzolanic effect which can help to enhance the mechanical and durability properties of the concrete and titanium dioxide also can reduce the pore structures of the concrete by filling up the minor void. In this research study, the fabrication of lightweight green concrete in this research study is incorporating with green colored waste glass powder with a particle size of 125 - 180 μm and TiO2 to reduce the usage of cement in the concrete production which can help to minimize the environmental problems and ground granulated blast furnace slag (GGBS) will act as the lightweight aggregate. In this research study, the properties of fresh concrete are determined by the flow table test, the mechanical properties of the concrete are determined by compressive strength test, flexural strength test and scanning electron microscopy test (SEM), the durability properties of the concrete are determined by water absorption test, porosity test, air permeability test, and chloride penetration test. The analysis of the results obtained from various lab test is used to compare the lightweight green concrete with the control concrete to investigate the effects of the substitution materials and improvement on properties of concrete. The optimum green lightweight concrete has been determined, and the optimum concrete is incorporating with 20% substitution portion of greencolored glass powder and 1% substitution portion of TiO2 for partial cement replacement. The optimum green lightweight concrete has achieved a compressive strength of 104 N/mm2 and excellent performance in the durability of concrete. Lastly, lightweight green concrete is successfully fabricated as a potential sustainable construction material in the near future.